ANALYSIS OF FACTORS ASSOCIATED WITH BOARDING TIME IN YELLOW ZONE OF EMERGENCY DEPARTMENT AT dr.ISKAK TULUNGAGUNG HOSPITAL - Fitrio Deviantony; Ahsan Ahsan; Setyoadi Setyoadi (NurseLine Journal, 2017)
Patient’s visits in the emergency room (ER) increase in number in every year. The increasing number of hospital visits is directly associated with the increasing number of patients who come to the emergency department. The increased number of patients resulted in the buildup of patients in the ER, especially in the Yellow Zone and causing the boarding time after the inpatient decision was decided to be longer. The purpose of this study was to analyze the problems related to variables that have a correlation with the boarding time of the patient after the decision of hospitalization is decided in the yellow zone of the emergency department at RSUD dr. Iskak Tulungagung. The method of this research was analytic observational research with cross sectional approach. The number of samples was 78 respondents. The sampling technique used nonprobability sampling. Pearson test and Spearman test were applied to identify the correlation between variables and multivariate linear regression test was used to find out the most dominant factor in influencing patient boarding time after the decision of hospitalization was made. The result of bivariate test showed the correlation between boarding time with room preparation time (p = 0.000), laboratory test results (p = 0.000), diagnostic time (p = 0.000), and ratio between nurse and patient (p = 0.000). Boarding time was not correlated with time of arrival (p = 0.263) and insurance coverage (p = 0.980). Multivariate analysis with linear regression obtained result of constant value (B = 681.212), ratio between nurse and patient (p= 0.000; B = -861.011), bed occupancy time (p= 0.000; B =0.620) and diagnostic time (p=0.022; B = 2.636). The implication of this research is to get a formula that able to shorten patient boarding time after the decision of hospitalization was made and can give a standart time for boarding time.